Percutaneous Coronary Intervention vs. Coronary Artery Bypass Grafting for Treating In-Stent Restenosis in Unprotected-Left Main: LM-DRAGON-Registry - Wańha, Wojciech; Bil, Jacek; Kołodziejczak, Michalina; Kowalówka, Adam; Kowalewski, Mariusz; Hudziak, Damian; Gocoł, Radosław; Januszek, Rafał; Figatowski, Tomasz; Milewski, Marek; Tomasiewicz, Brunon; Kübler, Piotr; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Data regarding management of patients with unprotected left main coronary artery in-stent restenosis (LM-ISR) are scarce. Objectives This study investigated the safety and effectiveness of percutaneous coronary intervention (PCI) vs. coronary artery bypass grafting (CABG) for the treatment of unprotected LM-ISR. Methods Consecutive patients who underwent PCI or CABG for unprotected LM-ISR were enrolled. The primary endpoint was a composite of major adverse cardiac and cerebrovascular events (MACCE), defined as cardiac death, myocardial infarction (MI), target vessel revascularization (TVR), and stroke. Results A total of 305 patients were enrolled, of which 203(66.6%) underwent PCI and 102(33.4%) underwent CABG. At 30-day follow-up, a lower risk of cardiac death was observed in the PCI group, compared with the CABG-treated group (2.1% vs. 7.1%, HR 3.48, 95%CI 1.01–11.8, p = 0.04). At a median of 3.5 years [interquartile range (IQR) 1.3–5.5] follow-up, MACCE occurred in 27.7% vs. 29.6% (HR 0.82, 95%CI 0.52–1.32, p = 0.43) in PCI- and CABG-treated patients, respectively. There were no significant differences between PCI and CABG in cardiac death (9.9% vs. 18.4%; HR 1.56, 95%CI 0.81–3.00, p = 0.18), MI (7.9% vs. 5.1%, HR 0.44, 95%CI 0.15–1.27, p = 0.13), or stroke (2.1% vs. 4.1%, HR 1.79, 95%CI 0.45–7.16, p = 0.41). TVR was more frequently needed in the PCI group (15.2% vs. 6.1%, HR 0.35, 95%CI 0.15–0.85, p = 0.02). Conclusions This analysis of patients with LM-ISR revealed a lower incidence of cardiac death in PCI compared with CABG in short-term follow-up. During the long-term follow-up, no differences in MACCE were observed, but patients treated with CABG less often required TVR. Visual overview A visual overview is available for this article. Registration https://www.clinicaltrials.gov; Unique identifier: NCT04968977.